Development and validation of competency-based research I workbook for distance learning - Frankie Aspira Fran (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
In a distance learning environment, the use of appropriate instructional material is an essential element of a successful teaching and learning process. Because of the pandemic, teachers were required to use the available learning resources to ensure learning continuity. In this paper, the main objective is to develop and validate instructional material that would assist teachers in delivering the lessons through a modular learning approach. A descriptive normative survey was utilized to determine the validity of the developed workbook for Research I. The results showed that the workbook met the prescribed requirements regarding adequacy, clarity, objectives, suitability, and usefulness. It was found to be adequate, clear, coherent, attainable, suitable, and useful for teachers and students as they discover learning through research. Thus, the workbook is recommended as instructional material in teaching the subject and promises a potential for a significant contribution to education and learning. Future research may also be explored, focusing on the effectiveness of the material developed